Dynamics of coral-associated bacterial communities acclimated to temperature stress based on recent thermal history. Issue 1 (December 2017) - Shiu, Jia-Ho; Keshavmurthy, Shashank; Chiang, Pei-Wen; Chen, Hsing-Ju; Lou, Shueh-Ping; Tseng, Ching-Hung; Justin Hsieh, Hernyi; Allen Chen, Chaolun; Tang, Sen-Lin
Abstract Seasonal variation in temperature fluctuations may provide corals and their algal symbionts varying abilities to acclimate to changing temperatures. We hypothesized that different temperature ranges between seasons may promote temperature-tolerance of corals, which would increase stability of a bacterial community following thermal stress.Acropora muricata coral colonies were collected in summer and winter (water temperatures were 23.4–30.2 and 12.1–23.1 °C, respectively) from the Penghu Archipelago in Taiwan, then exposed to 6 temperature treatments (10–33 °C). Changes in coral-associated bacteria were determined after 12, 24, and 48 h. Based on 16S rRNA gene amplicons and Illumina sequencing, bacterial communities differed between seasons and treatments altered the dominant bacteria. Cold stress caused slower shifts in the bacterial community in winter than in summer, whereas a more rapid shift occurred under heat stress in both seasons. Results supported our hypothesis that bacterial community composition of corals in winter are more stable in cold temperatures but changed rapidly in hot temperatures, with opposite results for the bacterial communities in summer. We infer that the thermal tolerance ranges of coral-associated bacteria, with a stable community composition, are associated with their short-term (3 mo) seawater thermal history. Therefore, seasonal acclimation may increase tolerance of coral-associated bacteria to temperature fluctuations.